Mesoscale geometric modeling of cellular materials for finite element analysis. Issue 6 (19th September 2017) - Bici, Michele; Campana, Francesca; De Michelis, Micaela
ABSTRACT: Mesoscale geometric modeling of cellular materials is not strictly related only to tomography reconstruction, but it can be applied also in Finite Element Analysis: (a) to better understand load distribution at the interfaces; (b) to develop and calibrate material models; (c) for sensitivity analysis to different loads or shape parameters. This paper aims to examine some of the most applied techniques for geometric modeling of cellular materials at a mesoscale level discussing their advantages and disadvantages for Finite Element Analysis. Among them, two of the most applied techniques, the Voronoi approach and the reverse engineering reconstruction, are here applied to simulate the behavior of aluminum foams under compression. These applications compared to some experimental evidences confirm the capability of mesoscale analysis, highlighting possible enhancement of the geometric modeling techniques. GRAPHICAL ABSTRACT: